Evaluation of the shielding parameters of alkaline earth based phosphate glasses using MCNPX code - Agar, O.; Khattari, Z.Y.; Sayyed, M.I.; Tekin, H.O.; Al-Omari, S.; Maghrabi, M.; Zaid, M.H.M.; Kityk, I.V. (Results in physics, 2019)
Glass systems of composition 16XO–3Al2O3–6CuO–20Na2O–55P2O5 (where X = Sr, Ca, Mg and Ba mol%) have been investigated to check its potential utilize as gamma ray shielding material. Different shielding quantities namely mass attenuation coefficient (µ/ρ), effective atomic number (Zeff), half value layer (HVL) and mean free path (MFP) have been evaluated using MCNPX code and XCOM program at different photon energies between 0.015 and 10 MeV. The obtained data revealed good agreement between the µ/ρ values derived from XCOM and MCNPX code (version 2.6.0). It is found that the mass attenuation coefficients of BaO-doped phosphate glass are higher than those of the other alkaline earth elements–doped glasses, whereas MgO possess the lowest values. This indicates that the BaO-doped phosphate glass is the superior gamma radiation attenuator among the studied glass samples. The gamma shielding performance of the glasses under study has been compared to some commercial glasses and different concrete samples in terms of MFP.